2012
DOI: 10.1155/2013/589354
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Component Adsorption of Benzene, Toluene, Ethylbenzene, and Xylene from Aqueous Solutions by Montmorillonite Modified with Tetradecyl Trimethyl Ammonium Bromide

Abstract: Multicomponent adsorption of benzene, toluene, ethylbenzene, and xylene (BTEX) was assessed in aqueous solutions by montmorillonite modified with tetradecyl trimethyl ammonium bromide (TTAB-Mt). Batch experiments were conducted to determine the influences of parameters including loading rates of surfactant, contact time, pH, adsorbate concentration, and temperature on the adsorption efficiency. Scanning electron microscope (SEM) and X-ray diffractometer (XRD) were used to determine the adsorbent properties. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
(75 reference statements)
3
37
0
1
Order By: Relevance
“…World experience [6][7][8][9][10][11] in the development of new technologies for water purification contaminated with organic substances, which are capable of forming stable emulsions, proves the expediency of the use of various types of natural disperse minerals (bentonite, glauconite or paligrosite clays). Clays can be used both in natural form and after special activation (modification of clay surface with surfactants or special inorganic substances).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…World experience [6][7][8][9][10][11] in the development of new technologies for water purification contaminated with organic substances, which are capable of forming stable emulsions, proves the expediency of the use of various types of natural disperse minerals (bentonite, glauconite or paligrosite clays). Clays can be used both in natural form and after special activation (modification of clay surface with surfactants or special inorganic substances).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Under conditions of a purification process at coke enterprises, such a low pH value is irrational (the reaction of the medium lies within the range of 7.3−8.3). The adsorption capacity of TTAB-Mt in relation to PAH decreases in the range of xylene>ethylbenzene>toluene>benzene [7]. It is naphthalene that defines physical and chemical properties of resins as the main component of an identified part of a chemical composition [8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…There was agreement between the q e calculated by the pseudo-second-order Modeling of adsorption of xylene onto AD-GNS a pseudo-second-order model; b intra-particle diffusion model kinetic model and the experimental q e , indicating that the pseudo-second-order model better represented the adsorption kinetics. Researchers have reported that the sorption of xylene with raw and thermally modified diatomite and TTAB-MT is well described by the pseudo-second-order model (Nourmoradi 2012). …”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Many absorbents can be used for adsorption of xylene from aqueous solutions, including carbon nanotubes, organoclay, activated carbon, diatomites, and nano-sorbents (Aivalioti et al 2012b;Lin and Huang 1999;Nourmoradi 2012). Nano-materials have interesting properties that differ from those of their corresponding bulk states which make them promising sorbents in aqueous solutions (Paraguay-Delgado et al 2005;cheng et al 2004).…”
Section: Introductionmentioning
confidence: 99%